(untitled) (Studia theodisca, 2019)
Johann Elias Schlegel’s writing for the theatre always pairs up with theoretical reflection. In his essays, Schlegel often takes an original stance with respect to his background as a member of the Gottsched circle. At no time does he ever set aside the mimetic principle; instead, he deploys it on behalf of an aesthetic of affects firmly anchored to a lucid understanding of the political and social situation surrounding the reception of his work. This study mainly focuses on how this intertwining finds expression in his essays and in his major tragedy Canut (1746).